Please take over: XAI, delegation of authority, and domain knowledge - Kevin Bauer; Moritz von Zahn; Oliver Hinz (Leibniz Institute for Financial Research SAFE, 2023)
Recent regulatory measures such as the European Union's AI Act require artificial intelligence (AI) systems to be explainable. As such, understanding how explainability impacts human-AI interaction and pinpointing the specific circumstances and groups affected, is imperative. In this study, we devise a formal framework and conduct an empirical investigation involving real estate agents to explore the complex interplay between explainability of and delegation to AI systems. On an aggregate level, our findings indicate that real estate agents display a higher propensity to delegate apartment evaluations to an AI system when its workings are explainable, thereby surrendering control to the machine. However, at an individual level, we detect considerable heterogeneity. Agents possessing extensive domain knowledge are generally more inclined to delegate decisions to AI and minimize their effort when provided with explanations. Conversely, agents with limited domain knowledge only exhibit this behavior when explanations correspond with their preconceived notions regarding the relationship between apartment features and listing prices. Our results illustrate that the introduction of explainability in AI systems may transfer the decision-making control from humans to AI under the veil of transparency, which has notable implications for policy makers and practitioners that we discuss.
Keywords: 330